SEROLOGICAL PREVALENCE OF HEPATITIS-B VIRUS (HBV) IN TEHSIL DARAZINDA SUB DIVISION DERA ISMAIL KHAN, KPK, PAKISTAN (The Research of Medical Science Review, 2025)
Hepatitis is the most common serious viral liver disease. It is a major threat to public health around the world. The purpose of this study was to determine the prevalence of HBV-positive patients in the general population of Tehsil Darazinda in district D.I. Khan, Pakistan, which is still unknown. A total of 519 blood samples were collected on the basis of signs and symptoms to investigate the infection rate of HBV in the study of population. Among these, 260 were female and 259 were male. All the HBV suspected participants were confirmed through ICT method, which was then confirmed using ELISA. The findings of the HBV DNA screening tests showed that ELISA-based results are more reliable and that positive cases of males account for 58 (22.93%) of the infection cases compared to females, who account for 47 (18%). the study included participants ranging in age from 1 to 75 years of age. The results of an age-wise analysis showed that people in the 16–45 age range are more likely to contract HBV DNA. The survey-based study on the frequency and risk factors linked to the spread of HBV infection found that married individuals had the highest prevalence of HBsAg (64.62%). On the other hand, individuals with a family record of HBV positivity carried the lowest rate of infection (1.43%). The additional factors associated with risk consisted of a history of orthodontic treatment (57.8%), surgical treatment (41.84%), blood transfusion or plasma (42.92%), ear, the nose, piercing, tattooing, or needle use (56.53%), frequent visits to a hairdresser shop (39.45%), and history of injection drug use (38.12%). This study demonstrates the alarming state of HBV circulation and emphasizes the need for improved planning, strategies, and policies to prevent and control HBV.